1994
DOI: 10.1037/0882-7974.9.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Repetition blindness and aging: Evidence for a binding deficit involving a single, theoretically specified connection.

Abstract: This study tested 2 main hypotheses for explaining repetition blindness (RB), a difficulty in encoding and recalling rapidly presented repeated words in sentences. Under 1 hypothesis, RB reflects an inhibitory process and should be more pronounced in young than in older Ss, who typically exhibit diminished inhibitory processes. Under the second hypothesis, RB reflects a failure to bind a specific connection: The second connection from the single node for encoding a repeated word is difficult to form under time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
7

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 28 publications
3
46
7
Order By: Relevance
“…The third surprising result in Altarriba and Soltano (1996) is the small (3%) and nonsignificant SB effect in the split-language sentences of Experiment IB, as compared with the much larger (9%) SB effect in MacKay and Miller (1994). On the basis of their nonsignificant result, Altarriba and Soltano concluded that their data "contradict" and "fail to support" the results of MacKay and Miller, a conclusion that is flawed on several counts.…”
Section: Nonoccurrence Of Reliable Sb In Split-language Sentencescontrasting
confidence: 41%
See 3 more Smart Citations
“…The third surprising result in Altarriba and Soltano (1996) is the small (3%) and nonsignificant SB effect in the split-language sentences of Experiment IB, as compared with the much larger (9%) SB effect in MacKay and Miller (1994). On the basis of their nonsignificant result, Altarriba and Soltano concluded that their data "contradict" and "fail to support" the results of MacKay and Miller, a conclusion that is flawed on several counts.…”
Section: Nonoccurrence Of Reliable Sb In Split-language Sentencescontrasting
confidence: 41%
“…Moreover, pretargets and targets in their materials were always in different languages, increasing the salience of translation equivalents in the repeated target condition, and thereby reducing SB. In contrast, MacKay and Miller's (1994) materials consisted of mixed-language sentences, where most of the words appeared in one language, but a variable number of words appeared in the other language, as in, say, "Mike aprendi6 to drive a car and began manejar to work" (translation: "Mike learned to drive a car and began to drive to work."). This mixed-language procedure is essential in attempting to equate the salience of the target (and its relation to the pretarget) in RB and SB sentences containing repeated versus unrepeated targets.…”
Section: Salience Ofrepeated Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, our hypothesis applies to phonology, whereas Zacks and Hasher (1997) exempt phonology and other automatic processes from age-linked inhibition deficits. Third, we define inhibition theoretically, whereas Hasher and Zacks define inhibition in terms of task-specific empirical effects (e.g., interference in negative priming and Stroop tasks), a problematic definition because processes other than inhibition can cause interference (see, e.g., MacKay, Miller, & Schuster, 1994).…”
Section: Aging and The Sequencing Of Phonological Segmentsmentioning
confidence: 99%